Sleep duration in the United States 2003–2016: first signs of success in the fight against sleep deficiency?. Issue 4 (8th January 2018) - Basner, Mathias; Dinges, David F
Abstract: Study Objectives: The high prevalence of chronic insufficient sleep in the population has been a concern due to the associated health and safety risks. We evaluated secular trends in sleep duration over the most recent 14-year period. Methods: The American Time Use Survey, representative of US residents ≥15 years, was used to investigate trends in self-reported sleep duration and waking activities for the period 2003–2016 ( N = 181335 respondents). Results: Sleep duration increased across survey years both on weekdays (+1.40 min/year) and weekends (+0.83 min/year, both p < .0001, adjusted models). This trend was observed in students, employed respondents, and retirees, but not in those unemployed or not in the labor force. On workdays, the prevalence of short (≤7 hr), average (>7–9 hr), and long (>9 hr) sleep changed by −0.44% per year ( p < .0001), −0.03% per year ( p = .5515), and +0.48% per year ( p < .0001), respectively. The change in sleep duration was predominantly explained by respondents retiring earlier in the evening. The percentage of respondents who watched TV or read before bed—two prominent waking activities competing with sleep—decreased over the same time period, suggesting that portions of the population are increasingly willing to trade time in leisure activities for more sleep. The results also suggest that increasing online opportunities to work, learn, bank, shop, and perform administrative tasks from home freed up time that likely contributed to increased sleep duration. Conclusions: The findings indicate first successes in the fight against sleep deficiency. Public health consequences of the observed increase in the prevalence of long sleep remain unclear and warrant further investigation.